Investigation of biomarkers to predict outcomes in allogeneic hematopoietic stem cell transplantation - Tachibana, Takayoshi; Miyazaki, Takuya; Matsumura, Ayako; Hagihara, Maki; Tanaka, Masatsugu; Koyama, Satoshi; Ogusa, Eriko; Aoki, Jun; Nakajima, Yuki; Takahashi, Hiroyuki; Suzuki, Taisei; Ishii, Yoshimi; et al. (Cytotherapy (Oxford, England), 2024)
•Biomarkers to predict outcomes were assessed from the clinico-statistical approach.•A prospective multicenter observational study was performed.•Six promising biomarkers were successfully identified and validated.•C-reactive protein to platelet ratio was a novel biomarker to predict transplant outcomes. Various biomarkers have been developed and evaluated to predict the prognosis and complications of allogeneic hematopoietic cell transplantation (HCT). Most previous studies conducted on different biomarkers evaluated single effects such as those associated with inflammation, immunology, iron metabolism, and nutrition, and only a few studies have comprehensively analyzed markers. The study aimed to survey comprehensive multiple markers prior to HCT and extract those that significantly predict the outcomes. A prospective multicenter observational study was performed. (UMIN000013506) Patients undergoing HCT for hematologic diseases were consecutively enrolled. Besides the usual clinical biomarkers, serum samples for extra-clinical biomarkers were collected and cryopreserved before starting the conditioning regimen. A total of 32 candidate biomarkers were selected, 23 from hematology, biochemistry, immunology, nutrition, and iron metabolism, and 9 from composite markers. Based on the area under the curve (AUC) values for survival, promising biomarkers was extracted. Internal validation for these markers was applied based on bootstrap methods. Setting the cut-off values for them, log-rank test was applied and outcomes including overall survival (OS), relapse, and non-relapse mortality (NRM) were evaluated using multivariate analyses. Furthermore, detailed analysis including transplant-related complications and external validation were conducted focusing on C-reactive protein (CRP) to platelet (Plt) ratio. A total of 152 patients with hematologic malignancies were enrolled from April 2014 to March 2017. CRP, soluble interleukin-2 receptor (IL2R), CRP to albumin (Alb) ratio, CRP to Plt ratio, Plt to IL2R ratio, and IL2R to Alb ratio were identified as promising markers. Internal validation successfully confirmed their reliability of AUC and multivariate analysis demonstrated the statistical significance between the higher and the lower markers. Above all, a higher CRP to Plt ratio was significantly associated with a lower OS (hazard ratio [HR] 2.77; 95% confidence interval [CI] 1.30−5.91; P = 0.008) and higher non-relapse mortality rates (HR 2.79; 95%CI 1.14−6.80; P = 0.024) at 180 days. Furthermore, univariate analysis showed that a higher CRP to Plt ratio was significantly associated with a higher incidence of sinusoidal obstructive syndrome (P < 0.001) and bloodstream infection (P = 0.027). An external validation test confirmed the significance of the CRP to Plt ratio for these outcomes. The multicenter prospective observational study successfully identified significant biomarkers in patients with hematologic malignancies who received HCT. In particular, CRP to Plt ratio was identified as a novel and useful biomarker for predicting transplant outcomes. Further investigations are needed to validate the novel markers, analysis of the pathophysiology, and application to treatment settings other than HCT.